THE EFFECT OF REGIONAL FUNDS AND REGIONAL TRANSFERS ON BASIC EDUCATION IN INDONESIA - Kurniasari, Windy; Jasmina, Thia (Universitas Islam Lamongan, 2023)
This study aims to analyze the effect of government budget for education consisting of regional funds and regional transfers on the quality of basic education in Indonesia as measured by the Education Quality Mapping (EQM) score. This study uses a cross-section regression method for 392 districts/cities in Indonesia. Based on the results, for both primary and junior secondary schools, local funds are statistically insignificant in influencing the PMP score. However, regional transfers significantly and positively affect the PMP score. Although not affecting the total PMP score for primary schools, regional funds significantly affect the PMP score through the standard of educators and education personnel (PTK); standard of facilities and infrastructure (sarpras); and standard of financing. As for junior secondary schools, regional funds affect the PMP score through the PTK standard. In addition, for regional transfers, at the primary level, regional transfers affect the PMP score through PTK standards, sarpras standards, management standards, financing standards, content standards and graduate competency standards (SKL). Meanwhile, at the junior high school level, regional transfers affect PMP scores through PTK standards, management standards, financing standards, assessment standards, content standards and SKL standards.